Bending angle prediction and control of soft pneumatic actuators with embedded flex sensors – A data-driven approach - Elgeneidy, Khaled; Lohse, Niels; Jackson, Michael (Mechatronics (Oxford), 2018)
•A purely data-driven approach for modelling the bending of soft pneumatic actuators.•Evaluation of the feedback from an embedded flex sensor at different operating conditions.•Accurate bending angle prediction at variable input pressures and even pressure leaks.•Comparing the prediction accuracy of regression analysis and neural network methods.•A PID controller is used to control the bending angle based on multi-sensory feedback. In this paper, a purely data-driven modelling approach is presented for predicting and controlling the free bending angle response of a typical soft pneumatic actuator (SPA), embedded with a resistive flex sensor. An experimental setup was constructed to test the SPA at different input pressure values and orientations, while recording the resulting feedback from the embedded flex sensor and on-board pressure sensor. A calibrated high speed camera captures image frames during the actuation, which are then analysed using an image processing program to calculate the actual bending angle and synchronise it with the recorded sensory feedback. Empirical models were derived based on the generated experimental data using two common data-driven modelling techniques; regression analysis and artificial neural networks. Both techniques were validated using a new dataset at untrained operating conditions to evaluate their prediction accuracy. Furthermore, the derived empirical model was used as part of a closed-loop PID controller to estimate and control the bending angle of the tested SPA based on the real-time sensory feedback generated. The tuned PID controller allowed the bending SPA to accurately follow stepped and sinusoidal reference signals, even in the presence of pressure leaks in the pneumatic supply. This work demonstrates how purely data-driven models can be effectively used in controlling the bending of SPAs under different operating conditions, avoiding the need for complex analytical modelling and material characterisation. Ultimately, the aim is to create more controllable soft grippers based on such SPAs with embedded sensing capabilities, to be used in applications requiring both a ‘soft touch’ as well as a more controllable object manipulation.